Effective physician retention strategies in Norway's northernmost county - Karin Straumea; Daniel MP Shawb
PROBLEM: Retaining physicians in remote settings can be challenging owing to the heavy workload and harsh environmental conditions and to the lack of opportunities for professional development. In Norway, poor physician distribution between urban and rural areas has been persistent, particularly in the north, where in 1997 a total of 28% of the primary care physician positions were vacant. APPROACH: Several corrective measures have been tried over the years. One was the establishment of a medical school in the northern city of Tromsø, which proved effective but did not avert new crises. A 1998 survey among primary care physicians signalled the need for new interventions conducive to professional development in rural areas. The existing medical internship and in-service training model for general practice were systematically adopted as tools for retaining physicians. LOCAL SETTING: In Finnmark - Norway's northernmost and most sparsely-populated county - medical practice is challenging, especially at the primary care level. In 1997, a 38% shortage of general practitioners (30 positions) threatened primary care safety. RELEVANT CHANGES: Almost twice as many medical interns as expected now take their first fully licensed job in the north of Norway. The post-training retention of primary care physicians after 5 years currently stands at 65%. LESSONS LEARNT: Postgraduate medical training can be conducted in remote areas in a manner that ensures professional development, counteracts professional isolation, and allows trainees and their families to grow roots in rural communities. Rural practice satisfies modern principles of adult learning (problem-based and attached to real-life situations) and offers excellent training conditions.